Performance of MAGNUM 2850 seeder in nontillage in the basaltic soil of Paraná, Brazil - Junior, Ruy Casão; Araújo, Augusto Guilherme de; Ralisch, Ricardo (Pesquisa Agropecuaria Brasileira, 2000)
The nontillage system has attained two million hectars in the State of Paraná, Brazil, in the last years, but one of the most important problems was the lack of suitable seeders to basaltic clay soils. Therefore, MAGNUM 2850 PD was studied as for energetic requirement and operational performance in order to fit it to the reality of the State of Paraná. It was observed that the traction power varied in function of moisture and of mechanical characteristics of the soil, and attained high values and high power demand in maximal situations – around 79.5 kW of the tractor. The soil coulter openers showed a good performance in cutting the vegetal and in depth uniformity of work; but they also showed a big mobilized area in the furrow. Good sowing quality was obtained, which was evaluated by the percentage and velocity of seed emergence in the field. Errors in seed quantity and deposition losses were identified, mainly in the acceleration speed of 8.0 km/h; but the transversal uniformity of seed deposition in the field was good.